A geometrical criterion for glass transition in soft-sphere fluids. Issue 34 (17th August 2018) - Zhou, Yuxing; Milner, Scott T.
Abstract : Supercooled monodisperse WCA fluids have been simulated using the crystal-avoiding method. After mapping to hard spheres, we find that the "T1-activity" (a geometrical criterion for neighbor rearrangement) of particles is correlated with glassy dynamics. Abstract : As glass-forming fluids become colder and denser, structural rearrangements become slow and eventually cease. For hard-sphere fluids, percolation of particles unable to change neighbors (T1-inactive particles) signals the glass transition. To investigate this geometrical criterion for mobility in soft-sphere systems, we simulate monodisperse fluids interacting with a generalized Weeks–Chandler–Andersen (WCA) potential in metastable equilibrium, using our previously developed crystal-avoiding method. We find that the vanishing diffusivity as the glass transition is approached can be described by a power law below the onset temperature of super-Arrhenius behavior. By mapping the soft spheres to hard spheres based on mean collision energy, we find that the diffusivity versus effective volume fraction curves collapse onto the hard-sphere curve for all systems studied. We find that the onset of super-Arrhenius behavior and the MCT dynamic glass transition correlate well with temperature when the T1-inactive particles form clusters of two particles on average and when the T1-inactive clusters percolate the entire system, respectively. Our findings provide new insight into the structural origin of glassy dynamics.